2013
DOI: 10.1504/jgba.2013.053561
|View full text |Cite
|
Sign up to set email alerts
|

Exploring online repurchase behavioural intention of university students in Malaysia

Abstract: The focus of this study is to explore the antecedents of online repurchase intention (RI) of university students in Malaysia. The aim of this study is to examine online RI, specifically to examine the impact of prepurchase user perceptions of attributes, pre-purchase user attitudes and postpurchase user attitudes on RI. This study managed to collect 318 completed online questionnaires from internet shoppers. Multiple Regression Analysis (Stepwise Method) was deployed to statistically test the proposed hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 95 publications
(148 reference statements)
6
24
0
1
Order By: Relevance
“…TAM is generally used in studies that investigate the adoption of technology by users and is said to be a dynamic and reliable model (Vijayasarathy, 2004). The TAM uses the TRA connection as a way to describe the acceptance of IT use (Rezaei and Amin, 2013). The main factors in the use of IT is said to include PU and the factor of PEOU (Liao and Hsieh, 2010) in which recent studies (e.g., Purnawirawan et al, 2012) take PU in exploring attitudes and intention of users.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…TAM is generally used in studies that investigate the adoption of technology by users and is said to be a dynamic and reliable model (Vijayasarathy, 2004). The TAM uses the TRA connection as a way to describe the acceptance of IT use (Rezaei and Amin, 2013). The main factors in the use of IT is said to include PU and the factor of PEOU (Liao and Hsieh, 2010) in which recent studies (e.g., Purnawirawan et al, 2012) take PU in exploring attitudes and intention of users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this study proposes a model of online repurchasing behaviour intention of university students based on TAM (Davis, 1989). A study (Rezaei and Amin, 2013) among Malaysian online shoppers found that PU and PEOU are positively significantly factors in predicting RI. This study considers a few studies' attempts to empirically examine the impact TAM behavioural constructs of PU and PEOU were tested for predicting user acceptance of the World Wide Web (WWW) regarding to implication of innovative retail.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, little attempts at conceptualizing loyalty and studying its antecedents are still being made (Haghkhah et al, 2013;Lam, Shankar, Erramilli, & Murthy, 2004;Rezaei & Amin, 2013;Roustasekehravani & Hamid, 2014). Generally there is not a field of theory in loyalty that is undefined.…”
Section: Introductionmentioning
confidence: 99%